The Role of The Students Association in The Promotion of Students' Speech Skills at The Khalid Bin Al Walid Institute at University of Muhammadiyah Mataram (ar) - Erwin Erwin; Nasarudin Nasarudin; Husnan Husnan (Universitas Islam Negeri Palangka Raya, 2019)
The purpose of this research is to explain the importance of the student organizations and describe their efforts to improve the speaking skills of students at the Mahad Khalid Bin Al Waleed at the University of Muhammadiyah Mataram. This research uses the qualitative approach with the descriptive type. The result shows the student organizations play an important role based on their objectives and functions. The objectives are to help the foundation and all parties in the Ma'had develop the students